2015
DOI: 10.3126/jsan.v2i2.13532
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine as an alternative to midazolam co-induction to propofol: a comparative study

Abstract: Background: Induction of anesthesia with propofol is known to produce systemic hypotension. Co-induction adds a small dose of other anesthetics to reduce the dose of induction agent to decrease hemodynamic disturbances. The aim of the study was to compare hemodynamic changes associated with Midazolam and ketamine as a coinduction agent with Propofol and to compare induction dose of Propofol following the co-induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…The study showed statistically significant difference between the two groups. 9 Ketamine group had least change in heart rate from baseline compared to midazolam group similarly, Srivastava et al 10 compared hemodynamic changes during induction using ketamine and midazolam as a co-induction agent to propofol among sixty-eight patients of ASA I and II undergoing elective surgery. They concluded that ketamine group had least change in heart rate from baseline which further supports our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed statistically significant difference between the two groups. 9 Ketamine group had least change in heart rate from baseline compared to midazolam group similarly, Srivastava et al 10 compared hemodynamic changes during induction using ketamine and midazolam as a co-induction agent to propofol among sixty-eight patients of ASA I and II undergoing elective surgery. They concluded that ketamine group had least change in heart rate from baseline which further supports our study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings like our study was seen in Yadav et al, Srivastava et al and Kalita A and Ahmed ALM. [9][10][11] They concluded that ketamine provides better hemodynamic stability as a co-induction agent.…”
Section: Discussionmentioning
confidence: 99%